Tocomin Restores Endothelium-Dependent Relaxation in the Diabetic Rat Aorta by Increasing NO Bioavailability and Improving the Expression of eNOS - Ali, Saher F.; Woodman, Owen L. (Frontiers in Physiology, 2019)
We investigated whether treatment with tocomin, a palm oil extract with a high content of tocotrienols, would preserve endothelial function in aortae isolated from type 1 diabetic rats. Wistar rats were injected with a single dose of streptozotocin (diabetic, 50 mg/kg) or citrate buffer (normal) to the tail vein. Rats were kept for 10 weeks and tocomin (40 mg/kg/day sc) or its vehicle (peanut oil) was administered for the last 4 weeks of that period. Aortae from diabetic rats had impaired endothelium-dependent relaxation that was associated with increased expression of the NADPH oxidase Nox2 subunit, increased generation of superoxide and decreased expression of eNOS in the vasculature. Tocomin, prevented the diabetes-induced changes in vascular function, reduced vascular superoxide production and reversed the changes in the expression of the eNOS protein. Using selective inhibitors of nitric oxide synthase (NOS), soluble guanylate cyclase (sGC) and calcium-activated potassium (KCa) channels we demonstrated that tocomin increased NO-mediated relaxation, without affecting the contribution of endothelium-dependent hyperpolarization to the endothelium-dependent relaxation. The beneficial actions of tocomin in this model of diabetes-induced endothelial dysfunction suggests that it may have potential to be used as a therapeutic agent to prevent vascular disease during diabetes.